THE SYSTEMATIC REVIEW OF OUTCOME AFTER RECONSTRUCTION OF THE PROXIMAL HUMERUS FOR TUMOR RESECTION - Ferdiansyah, Ricky; Pratama, Alvin; Yulanda Putra, Yosie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Orthopaedic oncologists often encounter malignant tumors of the proximal humerus, which are the third most common location for bone and soft tissue tumors. These tumors present more therapeutic difficulties in terms of local control and future repair than those in other locations. Each surgical techniques have advantages and disadvantages. It has different outcomes. The aim: This study aims to show the outcomes after reconstruction of the proximal humerus for tumor resection. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like PubMed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 125 articles, whereas the results of our search on ScienceDirect brought up 141 articles. The results of the search conducted by title screening yielded a total 26 articles for PubMed and 32 articles for ScienceDirect. We compiled a total of 29 papers, 12 of which came from PubMed and 17 of which came from ScienceDirect. We excluded 2 review articles, 9 duplicate articles, 1 non-full text article, and 2 articles having ineligible outcomes data. In the end, we included fifteen research that met the criteria. Conclusion: Reverse shoulder arthroplasty showed potential for best functional outcomes and no local recurrence occurred during follow-up period. Whereas endoprostheses and allograft-prosthesis showed lowest complications rates. However, further investigation is needed.